Management of rectal foreign body with endoscopic snare: a case report - Kishore, A. Sai; Jeyasekharan, S. Sabu; C., Nithila; Reddy, N. Pradeep (International Surgery Journal, 2018)
Foreign bodies in the rectum, although not much common present a challenging task to the surgeons for retrieval. Depending on the type and position they can cause anorectal trauma and perforative peritonitis. Diagnosis is usually by history, per rectal examination and radiography. Here authors present a 27-year-old male who came with history of insertion of candle into rectum to prevent bleeding from haemorrhoids. Perforative peritonitis was ruled out and manually tried to remove it and all attempts failed. He was posted for colonoscopy and it revealed 23cm long candle in the rectum with bleeding anal tag. The tip of candle extended into sigmoid colon. Polypectomy snare applied around the candle and foreign body was gently removed. Check colonoscopy revealed no significant injury. He was referred to psychiatry department and he was discharged the next day.